Hand, Foot and Mouth Disease: A case report - Sah, Vikash K (Janaki Medical College Journal of Medical Science, 2017)
Hand, foot & mouth disease (HFMD) is a common emerging infectious disease caused by intestinal viruses of the picornaviridae family. A strain of Coxsackie virus (A16, A5, A6) is chiefly instrumental for producing this condition however more severe form is caused by Enterovirus-71. Though HFMD is a mild disease and can often be effectively and competently managed in an outpatient setting, recent outbreaks in the western pacific region with fatal form of disease have attracted the concern about the clinical assessment and appropriate management of HFMD. Early detection and good clinical judgments not only can prevent the fatal progression but also can reduce overall morbidity and mortality regarding HFMD. I am presenting a case report of the afore mentioned disease and the subsequent early clinical manifestation of the fatal form of HFMD to enlighten on the nature of the disease so that early diagnosis and management of the condition can be carried out to halt the disease progression and prevention for the betterment of children especially under five years.Janaki Medical College Journal of Medical Sciences (2016) Vol. 4 (1): 59-64